Water Removal from LOHC Systems - Müller, Karsten; Aslam, Rabya; Fikrt, André; Krieger, Christoph; Arlt, Wolfgang (Hydrogen, 2020)
Liquid organic hydrogen carriers (LOHC) store hydrogen by reversible hydrogenation of a carrier material. Water can enter the system via wet hydrogen coming from electrolysis as well as via moisture on the catalyst. Removing this water is important for reliable operation of the LOHC system. Different approaches for doing this have been evaluated on three stages of the process. Drying of the hydrogen, before entering the LOHC system itself, is preferable. A membrane drying process turns out to be the most efficient way. If the water content in the LOHC system is still so high that liquid–liquid demixing occurs, it is crucial for water removal to enhance the slow settling. Introduction of an appropriate packing can help to separate the two phases as long as the volume flow is not too high. Further drying below the rather low solubility limit is challenging. Introduction of zeolites into the system is a possible option. Water adsorbs on the surface of the zeolite and moisture content is therefore decreased.
CRIS-Team Scopus Importer:2024-12-16
Keywords: dibenzyl toluene; drying; hydrogen storage; LOHC; phase separation; purification